The effects of employee piracy on the level of competitiveness of organizations - Farren, Su Sherrie
This study is about the effects of employee piracy on the level of competitiveness of organizations. It aims to describe employee piracy, identify the effects of this problem in the level of organizations' competitiveness and to find ways to solve the problem of employee piracy. It concentrates only on three selected private organizations here in Iloilo City with the total of 25 respondents. Employee Piracy exist in the organizations studied which commonly occurred through offering of better benefits to the employees by other organizations. In terms of compensation only few of the respondents were offered higher compensation by other organizations, namely performance bonuses, basic salaries, overtime pay, payment on holidays, travel allowance and profit sharing, Good working environment greatly influence employees in accepting the offer of other organizations. however employee piracy does not affect the image, work performance and the level of profitability of the organization. Therefore, employee piracy does not affect the level of competitiveness of the organization.